Ondas de spin em redes decoradas - Silva, Wanêssa Façanha da (2014)
Low-dimensional systems have attracted much attention lately due to systems such as graphene and carbon nanotubes. Such systems have great potential for technological applications. In particular the creation of electronic devices due to their specific electronic properties. In this sense , the study of other systems in low dimension becomes urgent. More specifically , the study of magnetic properties of materials at low dimensionality also brings great new features in the behavior of ferromagnetic systems . The behavior of spin waves in such systems may be important to the study of spintronic and the development of new devices and magnetic memories . Thus in this work we aim to study the behavior of ferromagnetic spin waves in two-dimensional systems . For two-dimensional systems we consider here two-dimensional networks decorated . The decorations are introduced to generate networks with more than one basic atom in the unit cell of the system to study the richness of the spectrum of spin waves due to these changes . At first deal with a superimposition of square networks where the displacement of these networks depends on the control parameters alpha and beta . We also use the superposition of a square on a hexagonal network.